Exercise Training Not Offered to Half of Surveyed European Patients with HF - Hoyle, Brian (MD Conference Express, 2014)
The results of the 41-country Exercise Training in Heart Failure study (ExTra HF), involving more than 76,000 patients, support an argument for the establishment of a therapeutic tool to improve exercise capacity, quality of life, and health outcome in patients with heart failure.